2018
DOI: 10.1007/978-3-319-92258-4_5
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Similarity Measure for Image Sequences

Abstract: Quantification of image similarity is a common problem in image processing. For pairs of two images, a variety of options is available and well-understood. However, some applications such as dynamic imaging or serial sectioning involve the analysis of image sequences and thus require a simultaneous and unbiased comparison of many images. This paper proposes a new similarity measure, that takes a global perspective and involves all images at the same time. The key idea is to look at Schatten-q-norms of a matrix… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Furthermore, the preliminary studies on the HMM model-based path planner showed that it is promising, but further research is required before its effectiveness in aiding surgeons can be reported. Other similarity measures and matching methods proposed in the literature [34,35] as well as other path planners mentioned in the literature, such as the Rapidly Exploring Random Trees (RRT) [36] and Probability Roadmap Planner (PRP) [37], may be investigated in future research. A comparison test with ORB-SLAM based methods may also be performed.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the preliminary studies on the HMM model-based path planner showed that it is promising, but further research is required before its effectiveness in aiding surgeons can be reported. Other similarity measures and matching methods proposed in the literature [34,35] as well as other path planners mentioned in the literature, such as the Rapidly Exploring Random Trees (RRT) [36] and Probability Roadmap Planner (PRP) [37], may be investigated in future research. A comparison test with ORB-SLAM based methods may also be performed.…”
Section: Discussionmentioning
confidence: 99%
“…The second experiment ( Figure 2) consists of two coronal slices from a DCE-MRI dataset of a human kidney (data courtesy of Jarle Rørvik, Haukeland University Hospital Bergen, Norway; taken from [3]). The deformation computed using our proposed model is able to significantly reduce the misfit in liver and kidney in the left half while accurately fixing the spinal cord at the right edge.…”
Section: Image Registrationmentioning
confidence: 99%
“…The above considerations suggest to choose rank F as a distance measure. In [2,3], Brehmer et al proposed to reformulate the rank minimization problem in terms of a relaxation of the rank function based on a so-called Schatten q-norm.…”
Section: Schatten Q-norm Based Image Similarity Measure D Sqmentioning
confidence: 99%
“…Recently, Guyader [8] and Brehmer [2,3] proposed groupwise registration methods for a sequence of images. The underlying assumption is that images are linearly dependent if they are aligned.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation